2021
DOI: 10.4162/nrp.2021.15.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Association between stress and dietary habits, emotional eating behavior and insomnia of middle-aged men and women in Seoul and Gyeonggi

Abstract: BACKGROUND/OBJECTIVES The study was performed to investigate the degree of perceived stress by sex in middle-aged people, and to provide basic data for appropriate nutrition education and interventional measures for middle-aged subjects through comparative analysis of association between stress and dietary habits, emotional eating behavior, and insomnia. SUBJECTS/METHODS A survey was conducted in 670 middle-aged subjects (320 men and 350 women) aged 40–64 years, resided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Higher levels of stress are associated with emotional eating, both in our report and shown in several others [ 33 , 43 , 44 ]. These reports have completed the picture by adding sleep disorders in the connection between stress and emotional eating.…”
Section: Discussionsupporting
confidence: 89%
“…Higher levels of stress are associated with emotional eating, both in our report and shown in several others [ 33 , 43 , 44 ]. These reports have completed the picture by adding sleep disorders in the connection between stress and emotional eating.…”
Section: Discussionsupporting
confidence: 89%
“… 27 Likewise, Choi et al consider that adequate nutritional education and stress management intervention measures are necessary for proper eating behavior and better lifestyle, considering that stress is positively correlated with emotional eating behavior. 28 …”
Section: Discussionmentioning
confidence: 99%
“…27 Likewise, Choi et al consider that adequate nutritional education and stress management intervention measures are necessary for proper eating behavior and better lifestyle, considering that stress is positively correlated with emotional eating behavior. 28 Interpersonal influences exerted by health professionals (nutrition, physical activity, psychology, and nursing) to increase commitment to health-promoting behavior in nursing students is effective in a short period. Similar studies have also shown that interventions to improve lifestyles have been effective in achieving behavior change in a short time in the educational setting, both in high school students 29,30 and college students.…”
Section: Discussionmentioning
confidence: 99%
“…It is presumed that the large-scale new infectious disease caused emotional problems such as depression and anxiety (22,23). Stress affects eating patterns and can lead to overeating or skipping meals (24). Moreover, overeating or skipping due to stress is highly likely to have a serious adverse impact on health by ultimately leading to obesity or weight loss (25).…”
Section: Discussionmentioning
confidence: 99%